3D DDD modelling of dislocation–precipitate interaction in a nickel-based single crystal superalloy under cyclic deformation. Issue 17 (13th June 2018) - Lin, Bing; Huang, Minsheng; Zhao, Liguo; Roy, Anish; Silberschmidt, Vadim; Barnard, Nick; Whittaker, Mark; McColvin, Gordon
Abstract: Strain-controlled cyclic deformation of a nickel-based single crystal superalloy has been modelled using three-dimensional (3D) discrete dislocation dynamics (DDD) for both [0 0 1] and [1 1 1] orientations. The work focused on the interaction between dislocations and precipitates during cyclic plastic deformation at elevated temperature, which has not been well studied yet. A representative volume element with cubic γ ′-precipitates was chosen to represent the material, with enforced periodical boundary conditions. In particular, cutting of superdislocations into precipitates was simulated by a back-force method. The global cyclic stress–strain responses were captured well by the DDD model when compared to experimental data, particularly the effects of crystallographic orientation. Dislocation evolution showed that considerably high density of dislocations was produced for [1 1 1] orientation when compared to [0 0 1] orientation. Cutting of dislocations into the precipitates had a significant effect on the plastic deformation, leading to material softening. Contour plots of in-plane shear strain proved the development of heterogeneous strain field, resulting in the formation of shear-band embryos.